The effect of the National Food Reserve Agency on maize market prices in Tanzania - Pierre, Guillaume; Pauw, Karl; Magrini, Emiliano (Wiley, 2018)
Tanzania's National Food Reserve Agency has a mandate to ensure food security through procuring, reserving and recycling grain (primarily maize) in a cost‐effective manner. This mandate excludes a price stabilization role. Procurement prices, based on production costs, are often set above market prices to encourage production. Several disbursements channels exist: grain provided free or at a discount to targeted vulnerable households; subsidized sales to millers; and sales to prisons or nongovernmental aid programs, typically at market‐related prices. Given the perception that these activities are distortive, we use time‐series econometrics to model maize price dynamics in select wholesale markets to capture the Agency's market impact. We find that its pricing strategy had an insignificant impact on prices during 2010/11–2014/15 despite a fairly significant presence in at least some regional markets. We recommend that the Agency reconsiders offering a price premium on procured maize or selling maize at discount to millers, as limited market spill‐over effects imply the benefits are captured by only a few, even though its practice of providing subsidized or free maize to vulnerable people is not in question. Furthermore, current storage capacity expansion plans are not required and inconsistent with its food security mandate.